Managerial Skills in the Face of Full Costing in SMEs: The Case of Senegal - Moussa Diouf (Global Journal of Management and Business Research, 2023)
The influence of the managerial competencies of the manager on the practice of full costs remains very little addressed in the management control literature especially in the context of SMEs This contribution aims to reinforce the existing work by examining the following question what are the managerial competences of the SME manager that explain the practice of full costs within SMEs